Impact Assessment of Ethno – Religious Conflicts on National Integration in Nigeria since Independence - Okoi, Ibiang O. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
This study on “Impact Assessment of Ethno-Religious Conflicts on National Integration in Nigeria: From 1960 to date” examined Nigeria’s two major collective glitches of ethnic/ethnicity and religious conflicts since independence and their implications on national integration and socio-economic development. It x-rayed both the immediate and remote factors typically responsible for the frequent resurgences of ethnic and religious conflicts that have bedevilled the country. The objective is to highlight the fact that resurgences of ethno–religious conflicts in the country have negatively affected the nation’s integration and developmental process. The historical methodology adopted for this research involved the use of only secondary sources which involved both published and unpublished works on ethnic/ethnicity and religious conflicts in Nigeria. In fact, evidence continues to show that Nigeria’s experiment with freedom of worship, association and federalism as enshrined in the constitution has compromised national unity, political stability and development. The study submits that ethnicity and religion in Nigeria can be effectively utilized to promote harmony and a peaceful co-existence. To this end, the research recommends national policy of inclusion, equity, tolerance and justice for all.